2014
DOI: 10.2478/s13533-012-0172-1
|View full text |Cite
|
Sign up to set email alerts
|

The state of the environment in Mexico

Abstract: Abstract:The present work evaluates the state of the environment in Mexico based on indicators of the present status of the country's natural resource management, social and economical conditions and anthropogenic modifications. The Mexican environment is interpreted as a spatially open system having a historical character that is essentially determined by the continual interaction between nature, society and economy. The landscape approach is followed, considering as units of territorial analysis each one of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 3 publications
0
7
0
3
Order By: Relevance
“…High ( (Carabias et al 2007;Anta-Fonseca et al 2008;Bollo-Manent et al 2014). Also, approximately 48% of the area covered by vegetation showed some level of degradation and desertification, and 6% of the BEUs analyzed were classified as having water bodies in critical states (Table 1).…”
Section: Indicatorsmentioning
confidence: 97%
See 3 more Smart Citations
“…High ( (Carabias et al 2007;Anta-Fonseca et al 2008;Bollo-Manent et al 2014). Also, approximately 48% of the area covered by vegetation showed some level of degradation and desertification, and 6% of the BEUs analyzed were classified as having water bodies in critical states (Table 1).…”
Section: Indicatorsmentioning
confidence: 97%
“…Evaluating the phenomenon of deforestation is complex because it has multiple origins and causes corresponding to various biophysical and socioeconomic conditions. In the evaluation of the State of the Environment for Mexico in the year 2008, Bollo‐Manent et al () identified 145 Biophysical Environmental Units (BEU). BEUs were assessed using 15 indicators for the management of natural resources, including those relevant to anthropic modification and socioeconomic status.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Almost half its territory is in an unstable to critically degraded environmental state based on biophysical, social, and economic indicators (Bollo Manent et al. ), which threatens ecosystem stability and human quality of life. The magnitude of historic and current trends of habitat loss and degradation indicates the importance of restoration as a key strategy to conserve biodiversity and promote human well‐being (Sarukhán et al.…”
Section: Methodsmentioning
confidence: 99%